Current directions and future perspectives from the third Nematostella research conference() - Tarrant, Ann M. (Zoology (Jena), 2014)
The third Nematostella vectensis Research Conference took place in December 2013 in Eilat, Israel, as a satellite to the 8th International Conference on Coelenterate Biology. The starlet sea anemone, N. vectensis, has emerged as a powerful cnidarian model, in large part due to the extensive genomic and transcriptomic resources and molecular approaches that are becoming available for Nematostella, which were the focus of several presentations. In addition, research was presented highlighting the broader utility of this species for studies of development, circadian rhythms, signal transduction, and gene–environment interactions.